THE UNBEARABLE LIGHTNESS OF INTERNATIONAL OBLIGATIONS: WHEN AND HOW TO EXERCISE JURISDICTION UNDER CANADA’S CRIMES AGAINST HUMANITY AND WAR CRIMES ACT - Lafontaine, Fannie (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional)

(untitled) (Société québécoise de droit international, 2010)
This study offers an analysis of “when” and “how” Canada may –or must– exercise jurisdiction over suspected perpetrators of genocide, crimes against humanity and war crimes. The first part looks at the legislative choices made in the Crimes against Humanity and War Crimes Act as to temporal, territorial and extraterritorial jurisdiction, including universal jurisdiction and the requirement of the presence of the accused on Canada’s territory, in light of the correlative rules and obligations of international law. The second part of the study is concerned with “how” Canada will –or should– decide to exercise jurisdiction. It describes the political safeguards put in place by the Act and assesses the criteria that guide –or should guide– the exercise of prosecutorial discretion. The “when” and the “how” are clearly intertwined. Indeed, the criteria upon which the Attorney General should base his or her decision to prosecute a person cannot– or should not– be dissociated from Canada’s international obligations and responsibilities in this regard. This study examines Canada’s approach regarding suspected war criminals present on its territory, which combines criminal and administrative remedies. It assesses some of the challenges it faces in living up to its commitment to fight impunity for the worst international crimes, in light of the “unbearable lightness” of international obligations.